PEMIKIRAN PENDIDIKAN ISLAM SYEKH BURHANUDDIN DALAM BUKU KARANGAN RAUF PAKIE MALANO DAN ABDUL MANAF - Ratna Kumala Dewi; Jarudin; Meri Erawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the reasons behind the researcher in conducting this study is the publication of a manuscript about Syech Burhanuddin stored in the National Library, the manuscript provides an important contribution in revealing the intellectual history of Islam in Minangkabau. In addition, Syech Burhanuddin is known as a central figure who introduced the first Islamic educational institution in the Minangkabau region, so that his existence has historical and pedagogical significance that deserves further exploration. Based on these considerations, the researcher is interested in raising a study with the title